O acesso à Eucaristia aos casais de segunda união: uma perspectiva ecumênica - Macedônio, Márcio André Orso (2012)
Family, as a divine institution, the basis of any society, has received impacts in the last few centuries, and one of them is the transference of the regulation of the matrimony to the State, that established the civil matrimony and, later, broke the Christian principle of the indissolubility of the matrimony, approving the Civil Divorce in 1977 and allowing any individual to end the marital bound. It represents a negative impact to the Christian Church, and, as a consequence, triggered a significant increase of couples that have divorced and that have a second matrimony. In order to solve many family conflicts, the divorce was approved by the State, and this is accepted by some ideologies and religions. However, the position of the Christian Church remains firm, considering the fight for the unit and indissolubility of the matrimony, which is defined as The matrimonial pact [Alliance], in which a man and a woman established a consortium to their lives, being not only positive to the couples as well as to the children s raising and, among baptized, the law was established by Jesus Christ, the Lord, that dignified the sacrament. Thus, among baptized, the same sacrament validates the matrimony and does not accept the second one (CIC 1055). The Catholic Church rejects the civil divorce of the Christians life, so that the catholic that has divorced and married again, is not allowed to participate of the Eucharist, since his/her situation is irregular. But the Evangelical Church Assembly of God does not conceive the civil divorce as the civil marriage, it follows the rules of the Bible and it is also belied in the indissolubility of the marriage, although the civil divorce is accepted, when the marital problem is infidelity, whose adultery of one spouse should be proved, and this is based on the Gospel of Saint Mathew 5.32, 19.9, and the word porneia is understood as prostitution and adultery. The exception to the rule of indissolubility allows the access of Lord s Supper, which is as real situation.